2019
DOI: 10.1212/nxi.0000000000000580
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica spectrum disorder

Abstract: ObjectiveTo gain insights into NMOSD disease impact, which may negatively affect QoL of patients, their families, and social network.MethodsThe current study used validated instruments to assess physical, emotional, and socioeconomic burden of NMOSD on QoL among 193 patients.ResultsA majority of patients reported an initial diagnosis of a disease other than NMOSD. Overall, two-thirds of patients reported NMOSD as having a strong negative impact on physical health (Short Form-36 [SF-36] score 27.1 ± 39.1), wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 44 publications
6
50
0
5
Order By: Relevance
“…In the majority of cases, NMOSDs are associated with serum immunoglobulin G (IgG) autoantibodies (Abs) targeting the astrocyte aquaporin-4 (AQP4) water channel (11,12). Patients typically suffer from recurrent attacks of severe optic neuritis and/or myelitis (13,14) and, less frequently, brainstem or brain involvement (15,16), leading to a diverse range of symptoms, of which severe pain is one of the most frequent and disabling (2,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Chronic pain occurs in NMOSD with an estimated prevalence between 72 and 86% (2,18,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…In the majority of cases, NMOSDs are associated with serum immunoglobulin G (IgG) autoantibodies (Abs) targeting the astrocyte aquaporin-4 (AQP4) water channel (11,12). Patients typically suffer from recurrent attacks of severe optic neuritis and/or myelitis (13,14) and, less frequently, brainstem or brain involvement (15,16), leading to a diverse range of symptoms, of which severe pain is one of the most frequent and disabling (2,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Chronic pain occurs in NMOSD with an estimated prevalence between 72 and 86% (2,18,27,28).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the primary fatigue in patients with MS may stem from centrally mediated processes caused by the conduction issues such as demyelination or axonal loss in CNS [7]. In NMOSD and MS, fatigue has been reported to impair activities of the daily living [6,[8][9][10]. In MS patients, the prevalence of fatigue was reported to be 50% to 90%, and more than 20 trials were performed to determine the appropriate treatment for fatigue [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…15,17,18 Depression and psychological distress affect subjective well-being in patients with NMOSD. [19][20][21][22] However, no studies have focused on stigma and NMOSD. The purpose of this study was to assess stigmatization and its impact on patients living with NMOSD.…”
Section: Introductionmentioning
confidence: 99%